Chinese Control Yuan: An Independent Supervisory Organ of the State - Herbert H. P. Ma (Washington University Law Quarterly, 1963)
The purpose of this Article is to introduce Western readers to the Control Yuan of the Republic of China. Although similar in purpose to the Ombudsman, the Control Yuan is a unique supervisory organ with roots in modern Chinese constitutional theory and in the traditional Chinese censorial administrative system.
Keywords: Constitutional law – China